C.1 - "Luard, Evan(ed.)" (London, 1970)
This book covers the following topics Frontier Disputes in Modern International; The league and territorial disputes; The United Nations and Frontier disputes; Regional Organizations and frontier disputes; Mediation and Judicial Settlement etc.
Keywords: International relations